Utility of whole‐exome sequencing for those near the end of the diagnostic odyssey: time to address gaps in care. Issue 3 (22nd September 2015) - Sawyer, S.L.; Hartley, T.; Dyment, D.A.; Beaulieu, C.L.; Schwartzentruber, J.; Smith, A.; Bedford, H.M.; Bernard, G.; Bernier, F.P.; Brais, B.; Bulman, D.E.; Warman Chardon, J.; et al.
Abstract : An accurate diagnosis is an integral component of patient care for children with rare genetic disease. Recent advances in sequencing, in particular whole‐exome sequencing (WES), are identifying the genetic basis of disease for 25–40% of patients. The diagnostic rate is probably influenced by when in the diagnostic process WES is used. The Finding Of Rare Disease GEnes (FORGE) Canada project was a nation‐wide effort to identify mutations for childhood‐onset disorders using WES. Most children enrolled in the FORGE project were toward the end of the diagnostic odyssey. The two primary outcomes of FORGE were novel gene discovery and the identification of mutations in genes known to cause disease. In the latter instance, WES identified mutations in known disease genes for 105 of 362 families studied (29%), thereby informing the impact of WES in the setting of the diagnostic odyssey. Our analysis of this dataset showed that these known disease genes were not identified prior to WES enrollment for two key reasons: genetic heterogeneity associated with a clinical diagnosis and atypical presentation of known, clinically recognized diseases. What is becoming increasingly clear is that WES will be paradigm altering for patients and families with rare genetic diseases.